Ear as Instrument. - Haworth, Christopher (Leonardo Music Journal, 2012)
The desire for instrumental qualities in computer music often leads the artist to a process of "synthetic limitation," wherein constraint is designed into a performance system, permitting creation only within prescribed limits. These practices can emerge as a consequence of the sheer dearth of possibilities available to the digital artist: as though the path to new sounds and ever more intimate control leads ultimately to a retreat. The author's response to this perennial dilemma has been to try to discover instrumental limitations within the ear itself. He describes an "ear-as-instrument" approach to the composition of Correlation Number One (CNO), an eight-channel computer music work he created in 2010 that uses a self-authored form of Distortion Product Oto-Acoustic Emission (DPOAE) synthesis.